Dynamic Mechanical Analysis of Borassus Husk Fiber Reinforced Epoxy: Evaluating Suitability for Advanced Aerospace and Automotive Applications - Md Atiqur Rahman; Mamadou Ndiaye; Bartosz Weclawski; Peter Farrell (Engineering Reports)
ABSTRACT This study investigates the effect of elevated temperatures on the mechanical properties of Borassus husk fiber‐reinforced epoxy composites, focusing on their potential for aerospace internal structural components. Composites were fabricated using Borassus husk fibers incorporated with epoxy resin, including 5% alkali‐treated fibers (treated for varying durations) to improve adhesion. Dynamic Mechanical Analysis (DMA) was performed according to ASTM D5418‐01 standards. Results revealed that both untreated and alkali‐treated fibers enhanced the storage modulus of the composites. The highest loss modulus was observed for the composite with 1‐h treated fibers. The glass transition temperature (Tg), determined from the peak loss modulus, was significantly higher (84°C–89°C) for treated Borassus husk fiber/epoxy composites compared to neat epoxy and composites reinforced with other natural fibers, such as flax, jute, palm sprout, date palm, sisal, and kenaf. Alkali treatment also notably increased the tan δ (damping factor), with the highest value (1.2) for the 0.75‐h treated fiber composite, outperforming several other natural fiber‐epoxy composites. Cole–Cole plots indicated improved resin‐fiber adhesion for composites containing 0.75‐ and 1‐h treated husk fibers. Phase angle data confirmed enhanced energy dissipation and viscoelastic behavior. Thermo‐mechanical stability improved, with the 0.75‐h treated fiber composite showing the lowest total mass loss (0.4%). Overall, alkali‐treated Borassus husk fiber composites exhibited superior mechanical stiffness, damping capacity, and thermal stability, making them ideal for aerospace and automotive applications requiring strength, impact resistance, and sustainability. It will also contribute to achieving the “net‐zero” target established in the 2015 Paris Agreement.